UPAYA MENINGKATKAN PENGETAHUAN CYBERBULLYING DI KALANGAN REMAJA MILENIAL DI SMAN 1 PLERET - Shulbi Muthi Sabila Salayan Putri (Jurnal Ilmiah Padma Sri Kreshna, 2019)
Cyberbullying is bullying happens in cyberspace mainly on social media. A form of cyberbullying is ridicule, threats, insults, or hacking. The phenomenon of cyberbullying and fatal consequences emerging from this action was suicidal. But cyberbullying that occur in Indonesia is still a trivial thing. Social medial cause few cases of cyberbullying increasing because of its characteristic that possible to spread information easily and fast. Socialization proper use of social media needs to be done to improve public awareness about the dangers of misuse of social media. The purpose of this service activity is to understand and apply the ethics in the use of social media as the current mainstream media among millennial teenagers, especially in the use of social media. As well as understanding the content and objectives in the ITE Law 11 of Article 27 of 2008 (Information and Electronic Transaction Law) for examples of cybercrime cases in the virtual world, especially cyberbully cases.